Agronomic performance of coffee in response to framework pruning in cycles of the “safra zero” - Lage Maia, Pedro; Silva Nadaleti, Denis; Botelho, Cesar; Botelho, Deila; Moreira, Priscila; Carvalho, Gladyston (Coffee Science - ISSN 1984-3909, 2020)
In this paper, we aimed at selecting genotypes of Coffea arábica L. that are responsive to framework prunin, with high productive potential and desirable agricultural features. We evaluated 18 progenies in the F5 generation, 8 of them being from the group Catucaí (breeding of seedlings of Red Catuaí with coffee seeds of the Icatu germplasm) and ten descendants from the Timor Hybrid (breeding of the Red and Yellow Catuaí with the Timor Hybrid), as well as two commercial cultivars as witnesses (Tupi IAC 1669-33 and Obatã IAC 1669-20). The experiment was carried out at the experimental field of the Federal University of Lavras. The coffee was pruned in August 2014 after the sixth crop and once again in August 2016, being two cycles in the “safra zero” system. The design used was in randomized blocks (RBD) with three repetitions and 20 treatments (18 progenies and two commercial cultivars) totaling 60 experimental plots. We evaluated the area under the progress curve of incidence and severity of leaf rust and cercosporiosis, the productivity (sacs há-1), sieve #16 and over (%), mocha-type grains (%) and apparent specific mass of grains (ton.m3). The genotype 12 (H516-2-1-1-18-1-4) was responsive to the framework pruning and kept its productivity stable in both pruning cycles, being efficient in such system of crop conduction, besides presenting low incidence and severity of coffee leaf rust and cercosporiosis and high sieve. Key words: Timor hybrid; Cercosporiosis; Leaf rust.